A study of teacher prediction and student performance - Bharath Raj J (Journal of All India Institute of Speech and Hearing, 1972)
It is generally assumed that the teacher is a good Predictor of the success orfailure of his students in the examination. A scientific enquiry into this problemwould be of interest. The question is whether the teacher by virtue of his experienceand close contact with the student would be a good judge or good predictor? And ifso, how accurate will his Predictions be?